ANALISIS PEMASARAN RUMAH SAKIT BERBASIS BUKTI - Sapardin, Aprildah Nur (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2021)
The annual growth rate of the private hospital sector increased rapidly by an average of 17.3%. The hospital management must make an effective marketing strategy to remain competitive, while still prioritizing quality health services and affordable to the community. The marketing mix is an example of an effective marketing strategy. One of the important elements of the marketing mix is physical evidence. The method used in writing this article is the Systematic Literature Review method by doing free searching on the Google Scholar website and the PubMed database using the keywords physical evidence, hospital physical evidence, mix marketing in hospital, and 7P mix marketing. Physical evidence is all about what customers see and experience when using a service and how they view the business. Physical evidence consists of three components, namely exterior facilities, interior facilities, and other tangible factors. The role of physical evidence is the packaging of services by conveying expectations and influencing perceptions, facilitating the flow of service delivery processes, providing information, facilitating the ordering process, managing consumers, socializing with employees and customers about the value they have, and providing a means for differentiation (differentiation). Some important aspects of physical evidence are the physical design of the hospital; amenities, signs, symbols, and artifacts; medical conditions; general condition of equipment and neat appearance of staff members; energy efficiency, and indoor air quality. Several studies have shown that the physical evidence component is the dominant factor in influencing patient satisfaction.